Controling Pelayanan Berbasis E-Government Dirumah Sakit Mamuju Tengah - Inayati, Mutia; Kadir, Abdul; Mone, Ansyari (Universitas Muhammadiyah Makassar, 2021)
This study aimed to determine e-government web presence services, e-government interactions, e-government transactions, and e-government transformation at Mamuju Tengah Hospital. This study used qualitative with the type of phenomonology. The number of informants was 7 people. Data collection techniques used observation, interview, and documentation methods. The results of this showed that the Web presence was running well and had performed web presence functions but in terms of Interaction in the medical record service or patient registration section there were still people not knowing the application provided, the transaction was still using a manual payment system or cas at patient, the transformation had not run well.